Improved learning outcomes of CNC programming through Augmented Reality jobsheet learning media - Febri Prasetya; Bayu Rahmadani Fajri; Budi Syahri; Fadhli Ranuharja; Aprilla Fortuna; Amri Ramadhan (invotek, 2021)
This study aims to determine: (1) the differences in learning outcomes of students who are taught using Augmented Reality (AR) jobsheet learning media with students taught using conventional learning media, (2) differences in learning outcomes of highly motivated students and low motivated students, and (3) the interaction between Project Based Learning learning methods and learning motivation in influencing learning outcomes. This research is a quasi-experimental research with a population of 64 people, the sample was taken as many as 32 people using the cluster random sampling method. Data were collected using a questionnaire for learning motivation and tests for learning outcomes. The data analysis technique used is descriptive analysis and two-way analysis of variance (Two Ways Anova). The research results found: 1) there are differences in student learning outcomes taught by the Project Based Learning learning method compared to student learning outcomes taught conventionally with Fcount of 7.98 (2) there are differences in learning outcomes of highly motivated students with low motivated students with Fcount 34.40, and (3) there is no learning interaction between learning methods and learning motivation in influencing student learning outcomes with Fcount 3.19